Two-dimensional torsional angle MoS2 based on cured sulfur regulation and preparation method thereof

Through the chemical vapor deposition method based on cured sulfur regulation, the problem of difficulty in efficient preparation of multi-layer two-dimensional torsion angle MoS2 in the prior art is solved, and high-quality and controllable layer-number preparation of MoS2 materials is achieved, with simple process and low cost.

CN119843242APending Publication Date: 2025-04-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510110740.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

It is difficult to efficiently prepare high-quality multi-layer two-dimensional torsion MoS2 in the prior art, and the CVD process is restricted by a variety of factors, resulting in greater difficulty in synthesis.

Method used

The chemical vapor deposition method based on cured sulfur regulation is adopted, and the number of curing times and reaction conditions of the sulfur source is accurately controlled, and the growth rate and crystal orientation of MoS2 are adjusted, thereby achieving efficient preparation of multi-layer torsion MoS2.

Benefits of technology

It realizes high-quality preparation of multi-layer torsion MoS2, with uniform material surface, no pollution, controllable number of layers, simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843242A_ABST
    Figure CN119843242A_ABST
Patent Text Reader

Abstract

The invention discloses two-dimensional torsional angle MoS2 based on cured sulfur regulation and control and a preparation method thereof, the method adopts a chemical vapor deposition method, and a multilayer torsional angle MoS2 material is successfully prepared by accurately regulating and controlling the curing frequency of a sulfur source. The preparation method is simple and convenient in process and low in cost, and the prepared multilayer torsional angle MoS2 has a uniform and flat surface, does not have secondary nucleation points and is high in material quality. The method is of great significance to controllable preparation and large-scale production of the torsion angle TMDCs, and lays a solid foundation for application of the two-dimensional torsion angle material in photoelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanomaterials and relates to a two-dimensional twisted-angle MoS2 regulated by solidified sulfur and a preparation method thereof. Background Art

[0002] Among two-dimensional materials, MoS2 shows great application potential in optoelectronics, catalysis and electronic devices due to its uniform surface structure, no dangling bonds, strong spin-orbit coupling and unique valley freedom. In recent years, with the continuous deepening of research on two-dimensional materials, it has been found that these materials show richer and more complex physical properties than single-layer and non-twisted multilayer two-dimensional materials when stacked at different rotation angles. These unique characteristics make two-dimensional materials have extremely broad application prospects in electronic devices, optoelectronic devices, spin electronics, energy conversion and storage. At present, the preparation technology of two-dimensional twisted MoS2 is mainly divided into two strategies: top-down and bottom-up. Compared with the top-down method, the bottom-up strategy represented by chemical vapor deposition (CVD) stands out with its unique charm and potential. First, CVD allows the desired twisted angle structure to be grown directly on the substrate in one step, reducing the contamination and interface defects that may be caused by subsequent processing steps, which is conducive to the preparation of large-area, continuous and highly uniform thin films, which is crucial for the development of high-performance electronic and optoelectronic devices. Secondly, by finely adjusting the reaction conditions (such as controlling the nucleation rate, increasing the reaction temperature, introducing air flow disturbance and ectopic nucleation, etc.), the growth rate, crystal orientation and even the final torsion angle of the material can be regulated to a certain extent, providing certain flexibility and designability. CN114959637A discloses a preparation method of a two-dimensional material torsion angle MoS2, which successfully prepares a double-layer torsion angle MoS2 with uniform surface, no pollution and high quality, but does not involve the preparation of multilayer torsion angle MoS2. Due to the CVD process being restricted by various factors, the synthesis of two-dimensional torsion angle MoS2 faces greater difficulty, therefore, the efficient preparation of two-dimensional torsion angle MoS2 is still very challenging. For this reason, the inventor, after intensive research, invented a method for preparing two-dimensional torsion angle MoS2 based on solidified sulfur regulation CVD method. Summary of the invention

[0003] The present invention provides a two-dimensional twisted-angle MoS2 with controllable number of layers and a preparation method thereof. The experimental process is simple, the raw materials are easy to obtain, and the prepared twisted-angle MoS2 has a clean surface, high quality, and controllable number of layers.

[0004] To achieve the above purpose, the following steps are specifically included:

[0005] A method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation, the preparation method comprising:

[0006] Step 1: The preparation space is a closed quartz tube, carrier gas is introduced into both ends of the quartz tube, a quartz crucible is placed at the inflow end of the carrier gas, and sulfur powder is placed in the quartz crucible;

[0007] Step 2: The Si surfaces of two SiO2 / Si substrates are laminated and stacked in a quartz test tube with openings at both ends, and a molybdenum source is placed in the tube, where the molybdenum source is located at the inflow end of the carrier gas;

[0008] Step 3: The quartz test tube and the quartz crucible are both located in the furnace of the heating furnace. The sulfur powder is composed of solidified sulfur powder and sulfur powder. The solidified sulfur powder needs to undergo 2 to 8 melting-solidification cycles. Each cycle includes heating the sulfur powder to 200° C. until it is completely melted, and then naturally cooling it to solidification. The amount of sulfur powder used is 1.0 to 3.0 g, of which the amount of solidified sulfur powder used is 0.6 to 1.8 g, and the amount of sulfur powder used is 1.0 to 2.4 g.

[0009] Step 4: Set the temperature control program, control the heating rate at 25℃ / min, and after the temperature reaches 800-820℃ at a uniform rate, carry out material growth, and then cool naturally to obtain multilayer twisted MoS2 on the SiO2 / Si substrate.

[0010] Optionally, the distance that the sulfur powder extends into the furnace is 1.8 to 2.0 cm.

[0011] Optionally, the molybdenum source is a mixture of molybdenum trioxide powder and NaCl particles, the amount of molybdenum trioxide powder is 1-2 mg, and the amount of NaCl particles added is 0.5-1 mg.

[0012] Optionally, the molybdenum source and the sulfur powder are 7 to 12 cm apart.

[0013] Optionally, the SiO2 / Si substrate is 1 cm away from the molybdenum source.

[0014] Optionally, in step 4, before starting heating, purge with Ar at a flow rate of 600 sccm; then adjust the carrier gas flow rate to a constant 40 sccm.

[0015] Optionally, the inner diameter of the quartz test tube is 10 mm; the outer diameter of the quartz tube is 25 mm.

[0016] Optionally, the cutting size of the SiO2 / Si substrate is 0.9 cm×3 cm.

[0017] Optionally, the growth time of the chemical vapor deposition is 5 to 10 minutes.

[0018] A two-dimensional twisted-angle MoS2 regulated by solidified sulfur is prepared by any of the preparation methods of the two-dimensional twisted-angle MoS2 regulated by solidified sulfur described in the present invention.

[0019] Advantages of the present invention:

[0020] (1) This method can prepare multilayer twisted-angle MoS2 in one step. The prepared multilayer twisted-angle MoS2 material has a uniform surface, is pollution-free, and has high quality. The preparation process is simple and easy to operate.

[0021] (2) The reaction process can achieve torsional nucleation and growth of materials by finely adjusting reaction conditions such as reaction temperature, reaction time, heating rate, etc., and provides flexibility and designability for the growth rate, nucleation density, etc. of the material.

[0022] (3) This method achieves the preparation of two-dimensional twisted MoS2 by precisely controlling the number of times the sulfur source is cured. The adjustment of the number of cures can precisely control the volatilization rate and concentration of sulfur, thereby optimizing the growth environment of MoS2, promoting the formation of twisted structures, and avoiding the formation of non-twisted structures caused by over-curing. High-quality, uniform two-dimensional twisted MoS2 materials can be obtained, providing a more reliable preparation method for its application in optoelectronics, electronic devices, and other advanced functional materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0024] Figure 1 It is a schematic diagram of the experimental preparation of the embodiments and comparative examples of the present invention;

[0025] Figure 2 This is an optical microscope photograph of Example 1 of the present invention;

[0026] Figure 3 is the Raman spectrum of Example 1 of the present invention;

[0027] Figure 4 The photoluminescence spectrum of Example 1 of the present invention;

[0028] Figure 5 This is an optical microscope photograph of Example 2 of the present invention;

[0029] Figure 6 is the Raman spectrum of Example 2 of the present invention;

[0030] Figure 7 The photoluminescence spectrum of Example 2 of the present invention;

[0031] Figure 8 This is an optical microscope photograph of Example 3 of the present invention;

[0032] Fig. 9is the Raman spectrum of Example 3 of the present invention;

[0033] Fig.10 The photoluminescence spectrum of Example 3 of the present invention;

[0034] Fig.11 This is an optical microscope photograph of Comparative Example 1 in the present invention. DETAILED DESCRIPTION

[0035] The present invention is described in detail below with reference to the accompanying drawings and specific implementation methods.

[0036] The present invention is based on the two-dimensional twisted angle MoS2 regulated by solidified sulfur, and is grown directly on a SiO2 / Si substrate by chemical vapor deposition. The twist angle of the two-dimensional twisted angle MoS2 is regulated by the sulfur source solidification regulation method, that is, by accurately controlling the number of solidification times of the sulfur source, and the two-dimensional twisted angle MoS2 material is obtained, which has a simple process and low cost.

[0037] The two-dimensional torsion angle MoS2 based on solidified sulfur regulation of the present invention achieves the regulation of the torsion angle by precisely controlling the number of solidification times of the sulfur source. The specific preparation includes:

[0038] Step 1: Place a certain amount of solidified sulfur powder in a quartz crucible, and then add a certain amount of fresh sulfur powder on top of it, making sure that the fresh sulfur powder covers the solidified sulfur powder. Place the quartz crucible in the heat radiation zone of a single temperature zone tube furnace.

[0039] Step 2: First, place two SiO2 / Si substrates in a quartz test tube with openings at both ends, then place evenly mixed molybdenum source and NaCl at the tube mouth, and place the quartz test tube in the center of a single-temperature zone tubular furnace.

[0040] Step 3: Seal the quartz tube and purge it with Ar at a flow rate of 600 sccm before starting heating. Then adjust the carrier gas flow rate to 40 sccm, and keep it constant during the entire chemical reaction.

[0041] Step 4: Set the temperature control program, control the heating rate at 25℃ / min, uniformly heat up to a maximum temperature between 800 and 820℃, and keep warm at this maximum temperature, then cool naturally to obtain two-dimensional twisted MoS2 on the SiO2 / Si substrate.

[0042] In the embodiment of the present disclosure, the solidified sulfur powder needs to undergo 2 to 8 melting-solidification cycles, each cycle includes heating the sulfur powder to 200°C until it is completely melted, and then naturally cooling it to solidify. This process is defined as a complete melting-solidification cycle. The amount of sulfur source used is 1.0 to 3.0 g, of which the amount of solidified sulfur powder used is 0.6 to 1.8 g, and the amount of fresh sulfur powder used is 1.0 to 2.4 g.

[0043] In the embodiment of the present disclosure, the inner diameter of the quartz test tube is 25 mm, the molybdenum source is molybdenum trioxide powder and NaCl particles, the amount of molybdenum trioxide powder is 1-2 mg, and the amount of NaCl particles added is 0.5-1 mg.

[0044] In the embodiment of the present disclosure, a sulfur source is placed in the quartz tube according to the flow direction of the carrier gas, and a quartz test tube with openings at both ends is arranged downstream of the sulfur source.

[0045] In the embodiment of the present disclosure, the cutting size of the SiO2 / Si substrate is 0.9 cm×3 cm.

[0046] In the embodiments of the present disclosure, two SiO2 / Si substrates are stacked with their silicon dioxide surfaces facing upward or downward, and a molybdenum source is placed 1 cm in front of the substrates. The molybdenum source is located near the gas inlet of the quartz tube.

[0047] In the embodiments of the present disclosure, the molybdenum source and the sulfur source are 7 to 12 cm apart.

[0048] In the embodiment of the present disclosure, the holding time of chemical vapor deposition is 5 to 10 minutes.

[0049] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, and the advantages of the present invention are reflected by analyzing the comparative examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0050] Embodiment 1:

[0051] This embodiment provides a method for preparing two-dimensional twisted-angle MoS2 on a silicon dioxide / silicon substrate, comprising the following steps:

[0052] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0053] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0054] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 1.2g of sulfur powder that has undergone two melting-solidification cycles into the quartz crucible as the S source, add 1.5g of fresh sulfur powder on top, and extend the quartz crucible into the furnace 2.0cm. The S source and the molybdenum source are 10cm apart, and heated in the center of the tubular atmosphere furnace for chemical vapor deposition of the two-dimensional material twisted angle MoS2, such as Figure 1 shown.

[0055] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 800℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Figure 2 shown.

[0056] Depend on Figure 2 Optical photos show that the prepared material is a double-layer twisted MoS2, with the twist angle of the first and second layers being 37°. Figure 3 As shown in the figure, both positions 1 and 2 have the Raman characteristic peaks of MoS2, indicating that the prepared material is MoS2. Figure 4 As shown, two peaks were observed at 1.81 eV and 1.93 eV, representing A excitons and B excitons respectively. The luminescence peak intensity of the single layer was greater than that of the double layer, indicating that the twisted angle structure of the double layer caused the change of the system band structure and caused the photoluminescence intensity to decay.

[0057] Embodiment 2:

[0058] This embodiment provides a method for preparing two-dimensional twisted-angle MoS2 on a silicon dioxide / silicon substrate, comprising the following steps:

[0059] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0060] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0061] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 1.2g of sulfur powder that has undergone 8 melting-solidification cycles into the quartz crucible as the S source, add 1.5g of fresh sulfur powder on top, and extend the quartz crucible 1.9cm into the furnace. The S source and the molybdenum source are 10cm apart, and heated in the center of the tubular atmosphere furnace for chemical vapor deposition of the two-dimensional material twisted angle MoS2, such as Figure 1 shown.

[0062] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 820℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Figure 5shown.

[0063] Depend on Figure 5 Optical photos show that the prepared material is a four-layer twisted MoS2, with the twist angles of the first and second layers being 39°, the second and third layers being 27°, and the third and fourth layers being 26°. Figure 6 As shown in the figure, positions 1, 2, 3, and 4 all have Raman characteristic peaks of MoS2, indicating that the prepared material is MoS2. Figure 7 As shown in the figure, two peaks are observed at 1.81eV and 1.93eV, representing A exciton and B exciton respectively. In four-layer twisted MoS2, the A exciton peak is the strongest in a single layer. As the number of layers increases from two layers to four layers, the position of the A exciton peak gradually moves to lower energy and the intensity gradually increases, while the peak position of the B exciton peak remains unchanged. This shows that the photoluminescence characteristics of four-layer twisted MoS2 are affected by the combined effects of the number of layers and the twist angle effect, showing exciton behavior different from that of single-layer materials.

[0064] Embodiment three:

[0065] This embodiment provides a method for preparing two-dimensional twisted-angle MoS2 on a silicon dioxide / silicon substrate, comprising the following steps:

[0066] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0067] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0068] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 1.2g of sulfur powder that has undergone 4 melting-solidification cycles into the quartz crucible as the S source, add 1.5g of fresh sulfur powder on top, and extend the quartz crucible 1.9cm into the furnace. The S source and the molybdenum source are 10cm apart, and heated in the center of the tubular atmosphere furnace for chemical vapor deposition of the two-dimensional material twisted angle MoS2, such as Figure 1 shown.

[0069] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 820℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Figure 8 shown.

[0070] Depend on Figure 8Optical photos show that the prepared material is a four-layer twisted MoS2, with the twist angles of the first and second layers being 82°, the second and third layers being 77°, and the third and fourth layers being 16°. Fig. 9 As shown in the figure, positions 1, 2, 3, and 4 all have Raman characteristic peaks of MoS2, indicating that the prepared material is MoS2. Fig.10 As shown in the figure, the peak intensity of the single layer is greater than that of the two, three, and four layers. Two peaks are observed at 1.81eV and 1.93eV, representing A excitons and B excitons, respectively. As the number of layers increases from two layers to four layers, the position of the A exciton peak gradually moves to lower energy, while the peak position of the B exciton peak remains unchanged. This indicates that the twist angle structure causes changes in the system's band structure and causes the photoluminescence intensity to decay.

[0071] Comparative Example 1:

[0072] This comparative example provides a method for preparing a two-dimensional MoS2 material using an over-cured sulfur source, comprising the following steps:

[0073] Step 1: Cut the silica / silicon substrate into 0.9×3 cm sheets and blow them clean with an air gun. Place the silica surfaces back to back in a quartz test tube with openings at both ends and an inner diameter of 10 mm.

[0074] Step 2: Add 1 mg of molybdenum trioxide powder and place it 1 cm from the front of the substrate, and add 1 mg of NaCl to the molybdenum trioxide powder.

[0075] Step 3: Place the quartz test tube in a quartz tube with an outer diameter of 25 mm, add molybdenum trioxide powder and one end of NaCl close to the air inlet. Put 1.2g of sulfur powder that has undergone 10 melting-solidification cycles into the quartz crucible as the S source, add 1.5g of fresh sulfur powder on top, and extend the quartz crucible 1.9cm into the furnace. The S source and the molybdenum source are 10cm apart, and heated in the center of the tubular atmosphere furnace for chemical vapor deposition of the two-dimensional material twisted angle MoS2, such as Figure 1 shown.

[0076] Step 4: Pass 600 sccm of argon gas for 10 minutes to completely remove the residual oxygen in the tube. Then continue to pass 40 sccm of argon gas, heat the tubular atmosphere furnace to 820℃ at a heating rate of 25℃ / min, and keep it warm for 5 minutes. Then cool it naturally to room temperature. The optical photo of the two-dimensional material MoS2 obtained at this time is as follows Fig.11 shown.

[0077] Compared with Example 2, it can be seen that when an over-cured sulfur source is used to prepare a two-dimensional MoS2 material, when other conditions remain unchanged, the material prepared on the substrate is an ultra-multilayer irregularly shaped non-twisted MoS2.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation, characterized in that: The preparation method comprises: Step 1: The preparation space is a closed quartz tube, carrier gas is introduced into both ends of the quartz tube, a quartz crucible is placed at the inflow end of the carrier gas, and sulfur powder is placed in the quartz crucible; Step 2: The Si surfaces of two SiO2 / Si substrates are laminated and stacked in a quartz test tube with openings at both ends, and a molybdenum source is placed in the tube, where the molybdenum source is located at the inflow end of the carrier gas; Step 3: The quartz test tube and the quartz crucible are both located in the furnace of the heating furnace. The sulfur powder is composed of solidified sulfur powder and sulfur powder. The solidified sulfur powder needs to undergo 2 to 8 melting-solidification cycles. Each cycle includes heating the sulfur powder to 200° C. until it is completely melted, and then naturally cooling it to solidification. The amount of sulfur powder used is 1.0 to 3.0 g, of which the amount of solidified sulfur powder used is 0.6 to 1.8 g, and the amount of sulfur powder used is 1.0 to 2.4 g. Step 4: Set the temperature control program, control the heating rate at 25℃ / min, and after the temperature reaches 800-820℃ at a uniform rate, carry out material growth, and then cool naturally to obtain multilayer twisted MoS2 on the SiO2 / Si substrate.

2. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1, characterized in that: The distance that the sulfur powder extends into the furnace is 1.8 to 2.0 cm.

3. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1 or 2, characterized in that: The molybdenum source is a mixture of molybdenum trioxide powder and NaCl particles, the amount of molybdenum trioxide powder is 1-2 mg, and the amount of NaCl particles added is 0.5-1 mg.

4. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1 or 2, characterized in that: The molybdenum source and the sulfur powder are 7 to 12 cm apart.

5. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1 or 2, characterized in that: The SiO2 / Si substrate is 1 cm away from the molybdenum source.

6. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1 or 2, characterized in that: In the fourth step, before starting heating, purge with Ar at a flow rate of 600 sccm; then adjust the carrier gas flow rate to a constant 40 sccm.

7. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1 or 2, characterized in that: The inner diameter of the quartz test tube is 10 mm; The outer diameter of the quartz tube is 25 mm.

8. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1 or 2, characterized in that: The cutting size of the SiO2 / Si substrate is 0.9 cm×3 cm.

9. The method for preparing two-dimensional twisted-angle MoS2 based on solidified sulfur regulation according to claim 1 or 2, characterized in that: The growth time of the chemical vapor deposition is 5 to 10 minutes.

10. A two-dimensional twisted-angle MoS2 regulated by solidified sulfur, characterized in that: It is prepared by the preparation method of two-dimensional twisted-angle MoS2 based on solidified sulfur regulation as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation of two-dimensional material torsional angle MoS2 and two-dimensional material torsional angle MoS2

    CN114959637A